THz Measurements, Antennas, and Simulations: From the Past to the Future - Fawad Sheikh; Andreas Prokscha; Johannes M. Eckhardt; Tobias Doeker; Naveed A. Abbasi; Jorge Gomez-Ponce; Benedikt Sievert; Jan Taro Svejda; Andreas Rennings; Jan Barowski; Christian Schulz; Ilona Rolfes; et al. (IEEE Journal of Microwaves, 2023)
In recent years, terahertz (THz) systems have become an increasingly popular area of research thanks to their unique properties such as extremely high data rates towards Tb/s, submillimeter localization accuracy, high resolution remote sensing of materials, and remarkable advances in photonics and electronics technologies. This article traces the progress of THz measurements, antennas and simulations, from historical milestones to the current state of research and provides an outlook on the remaining challenges.